Analyses of steady and unsteady thermal behaviour of simulated electronic chips in a liquid cooled vertical rectangular channel - Himangshu Bhowmik (2008)
Steady-state and transient experiments are performed to study the single-phase heat transfer from four in-line simulated electronic chips in a vertical rectangular channel using water and FC-72 as the working fluids. The steady-state experimental data covers a laminar flow regime with Reynolds number based on channel hydraulic diameter and Reynolds number based on heater length ranging from 0 to 2220 and 0 to 2775 respectively. The heat flux ranges from 0.1 W/cm2 to 2.6 W/cm2 for steady- state mixed and forced convection heat transfer and 0.1 W/cm2 to 0.6 W/cm2 for steady-state natural convection heat transfer.